In situ formation of reduced graphene oxide structures in ceria by combined sol–gel and solvothermal processing - Yang, Jingxia; Ofner, Johannes; Lendl, Bernhard; Schubert, Ulrich (Beilstein Journal of Nanotechnology, 2016)
Raman and IR investigations indicated the presence of reduced graphene oxide (rGO)-like residues on ceria nanoparticles after solvothermal treatment in ethanol. The appearance of such structures is closely related to cerium tert-butoxide as precursor and ethanol as solvothermal solvent. The rGO-like residues improve the catalytic CO oxidation activity. This was also confirmed by introduction of “external” graphene oxide during sol–gel processing, by which the rGO structures and the catalytic activity were enhanced.
Keywords: ceria; CO oxidation; graphene oxide; sol–gel processing